اللغة مؤسسة لا نظير لها ( إن ألحقنا بها الكتابة) الكتابة بوصفها من قضايا التفكير النّظري عند دي سوسير: Le langage est une institution sans analogue (si l’on y joint l’écriture) "l’écriture comme Problème dans la réflexion théorique de Saussure" - Djili Mohamed Zine, Mohamed Zine (Maalim, 2025)
Writing is a subject to which Saussure has paid close attention throughout his career. However, many thoughts developed on the topic by the linguist in his manuscripts do not fully emerge in the )Cours de linguistique générale(. This article aims to elaborate on the evidence of Saussure’s careful considerations on the subject of writing, which are inherited from the reading of the Cours de linguistique générale. It attempts to show that, because it allows linguistic and semiological approaches, writing is one of the major issues among Saussure’s thoughts. Also, it focuses on one of the questions that the linguist details in his writings: the analogy between the system of language and the system of writing. This article invites to explore anew the topic of writing in Saussure’s works taking into account the diversity of views developed by the linguist on this subject, and the diversity of the writing systems he studies.